2017
DOI: 10.3897/zookeys.656.11440
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding and species delimitation of Chaitophorinae (Hemiptera, Aphididae)

Abstract: Chaitophorinae aphids are widespread across Eurasia and North America, and include some important agricultural and horticultural pests. So, accurate rapid species identification is very important. Here, we used three mitochondrial genes and one endosymbiont gene to calculate and analyze the genetic distances within different datasets. For species delimitation, two distance-based methods were employed, threshold with NJ (neighbor-joining) and ABGD (Automatic Barcode Gap Discovery), and two tree-based approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 77 publications
1
21
0
Order By: Relevance
“…According to our results, the choice of GMYC method of lineage‐based to delimit species was more efficient than distance method and clearly, for the morphospecies, the COI lineage‐based GMYC approach supports conclusions that would not always be supported by comparison of distance. Authors such Zhu, Chen, Chen, Jiang, and Qiao () and Yu, Rao, Matsui, and Yang () also compared distance‐based methods with GMYC approach in their datasets and concluded that GMYC method presented higher accuracy on delimiting species.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the choice of GMYC method of lineage‐based to delimit species was more efficient than distance method and clearly, for the morphospecies, the COI lineage‐based GMYC approach supports conclusions that would not always be supported by comparison of distance. Authors such Zhu, Chen, Chen, Jiang, and Qiao () and Yu, Rao, Matsui, and Yang () also compared distance‐based methods with GMYC approach in their datasets and concluded that GMYC method presented higher accuracy on delimiting species.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the usability of DNA barcoding in aphid species identification has been tested in several studies [12,[41][42][43][44][45]. In aphid species, researchers used DNA barcoding for exploring species diversity [45], identification of species with morphological ambiguity and detection of cryptic species [41,43,[46][47][48], and even phylogenetic relationships [49,50]. Most of the DNA barcode sequences from previous studies or barcoding projects of aphids have been submitted to publicly available databases such as GenBank and the Barcode of Life Data Systems [51].…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial cytochrome oxidase c subunit 1 (COI) gene is considered to be the most suitable molecular marker that determines genetic distances among aphid species (Komazaki et al, 2010;Lee et al, 2011;Shufran and Puterka, 2011;Rebijith et al, 2013;Coeur d' Acier et al, 2014;Rakauskas, 2014;Chen et al, 2016;Zhu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The coding region of the COI gene was 605 bp, which included 40 variable sites, 565 conserved sites, 37 singletons, and 3 parsimonyinformative sites (219th, 300th, and 321st nucleotides). The sequences in all M. cerasi populations had an average nucleotide composition of 41.3% T, 33.9% A, 12.8% C, and 12.1% G. Commonly, the majority of the nucleotide composition in aphids is composed of adenine and thymine (Rebijith, 2013;Rakauskas et al, 2014;Zhu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation